we can write the above code as like this \(y = (( (u-t) * v) + w) * (t-z)\). so total variables are 6.

for more details...

Let x = u - t; ................1

y = x * v; ...............2

x = y + w; ..............3

y = t - z; ..............4

y = x * y;..............5

follow the sequence put 1 in 2., put 2 in 3, put 3&4 in 5. now you get the result as it was by written by me as above.

we can write the above code as like this \(y = (( (u-t) * v) + w) * (t-z)\). so total variables are 6.

for more details...

Let

x = u - t; ................1

y = x * v; ...............2

x = y + w; ..............3

y = t - z; ..............4

y = x * y;..............5

follow the sequence put 1 in 2., put 2 in 3, put 3&4 in 5. now you get the result as it was by written by me as above.